2022
DOI: 10.1155/2022/6292823
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Emerged Pulmonary Lophomoniasis due to Lophomonas blattarum among Hospitalized Patients in Southwestern Iran: A National Registry-Based Study

Abstract: Objectives. Lophomonas protozoan is an emerging pathogen transmitted through arthropods such as cockroaches. Lophomoniasis is still a mysterious disease with many unknown epidemiological aspects. The current study aimed to determine the prevalence of lophomoniasis among patients who were hospitalized in Hajar Hospital, Shahrekord, southwestern Iran, using a conventional PCR technique. Methods. In this retrospective study, 132 frozen bronchoalveolar lavage fluid (BALF) specimens from patients with respiratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…We also report a significantly higher number of radiological findings involving bronchi, alveoli, and pleura in chest tomography compared to other reports [1,4,16]. Unfortunately, we did not have a clear record of findings during bronchoscopy, which has also been reported to display abnormalities in the bronchial mucosa [3]. Overall, our patients appear to display a more severe lung infection related to Lophomonas, although this could be justified by a higher severity of pre-existing or ICUacquired illness at the time of the onset of a new respiratory tract infection, such as sequelae from SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…We also report a significantly higher number of radiological findings involving bronchi, alveoli, and pleura in chest tomography compared to other reports [1,4,16]. Unfortunately, we did not have a clear record of findings during bronchoscopy, which has also been reported to display abnormalities in the bronchial mucosa [3]. Overall, our patients appear to display a more severe lung infection related to Lophomonas, although this could be justified by a higher severity of pre-existing or ICUacquired illness at the time of the onset of a new respiratory tract infection, such as sequelae from SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 66%
“…Two case reports have been published showing co-infection with Lophomonas and cavitated pneumonia secondary to Mycobacterium tuberculosis [21,22]. It is likely that the presence of structural damage to normal lung anatomy may also facilitate the propagation of active protozoa and a steady clinical deterioration in these patients through a local inflammatory response, a finding that has been reported already reported by Mokhtarian et al, which reported that the commonest comorbidity on his patient sample was chronic bronchitis [3].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The sequence is 99% identical to previously published Pentatrichomonas hominis sequences. The other 17 sequences (MN243135–MN243136, MZ093069–MZ093079, OL477421–OL477423, and OL477431) were obtained by PCR from human bronchoalveolar lavage fluid or nasal secretions using primers designed to match the sequence from Thailand and L. striata (Fakhar et al, 2019, 2021; Mokhtarian et al, 2022). In our phylogenetic analyses, all of these sequences robustly branch within Trichomonadida (Figure 1F), either sister to P. hominis or with Tetratrichomonas .…”
Section: Resultsmentioning
confidence: 99%
“…However, ciliated epithelial cells, and fragments of them called ciliocytophthoria, look superficially like L. blattarum under the light microscope (Gelardi & Ciprandi, 2019), leading some authors to question the identification of Lophomonas in medical case studies (Li & Gao, 2016;Martínez-Girón & van Woerden, 2014). Recent studies claim to have confirmed the diagnosis of L. blattarum infection by molecular methods (Fakhar et al, 2019(Fakhar et al, , 2021Mokhtarian et al, 2022), but the short fragments of the 18S rRNA gene produced in these studies are highly similar to the Trichomonadida Pentatrichomonas or Tetratrichomonas, which are evolutionarily distant from Lophomonadida (Čepička et al, 2017).…”
mentioning
confidence: 99%